2021
DOI: 10.3390/atmos13010018
|View full text |Cite
|
Sign up to set email alerts
|

Screening Approach for Short-Term PM2.5 Health Co-Benefits: A Case Study from 15 Metropolitan Cities around the World during the COVID-19 Pandemic

Abstract: Fifteen cities across the world have been selected to investigate the public health co-benefits of PM2.5 reduction, during a period when various non-pharmaceutical interventions (NPIs) were adopted in the COVID-19 pandemic. Through applying a public health model, AirQ+, substantial spatial variations of global public health co-benefits were identified. Differences in seasonal air quality and population baselines were key underlying factors. For cities in North America, NPIs were introduced during the low pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Nonetheless, though a comparison is conducted between the WFH and NWFH participants in this study, it does not mean that only teleworkers can benefit from the WFH arrangement. As negative externalities, such as air pollution, fuel consumption, and carbon emissions, can be alleviated under WFH arrangements ( Lam et al, 2021 , Zhang et al, 2021 ), it is anticipated that the wider community can also benefit from the promotion of WFH. In the future, the impact of WFH arrangements on non-teleworkers may need to be more carefully examined.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, though a comparison is conducted between the WFH and NWFH participants in this study, it does not mean that only teleworkers can benefit from the WFH arrangement. As negative externalities, such as air pollution, fuel consumption, and carbon emissions, can be alleviated under WFH arrangements ( Lam et al, 2021 , Zhang et al, 2021 ), it is anticipated that the wider community can also benefit from the promotion of WFH. In the future, the impact of WFH arrangements on non-teleworkers may need to be more carefully examined.…”
Section: Discussionmentioning
confidence: 99%
“…Around three-quarters of the studies using either AirQ or AirQ+ focused on research-related questions (Supplementary Figure S4, Supplementary Tables S2, S3), followed by policy planning (2% of studies that used AirQ and 15% for AirQ+), the impact assessment of sand and dust storms in various cities of Iran and Poland (14 studies using either AirQ or AirQ+) [15,[23][24][25][26][27][28][29][30][31][32][33][34][35], and assessment of the impact of COVID-19 on air quality and health (5 studies) [36][37][38][39][40]. Individual studies assessed the impact of AP episodes or extreme events, such as (Indian monsoon [13,31] or large forest fires and megafires in the center region of Portugal [41]), and the use of residential wood combustion in cities of Sweden, Finland, Norway, and Denmark [42].…”
Section: Motivation Of Conducted Studiesmentioning
confidence: 99%
“…All but six studies that applied AirQ did not report which type of AQMSs were used [47,[53][54][55][56][57]. For AirQ+, 74% of the studies (65 out of 88) gathered AAP data from the AQMSs, and only 16 studies reported the types of AQMSs used (Supplementary Tables S2, S3) [25,31,36,39,41,[58][59][60][61][62][63][64][65][66][67][68].…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Around three-quarters of the studies using either AirQ or AirQ+ focused on research-related questions (Supplementary Figure S4, Supplementary Tables S2, S3), followed by policy planning (2% of studies that used AirQ and 15% for AirQ+), the impact assessment of sand and dust storms in various cities of Iran and Poland (14 studies using either AirQ or AirQ+) [15,[23][24][25][26][27][28][29][30][31][32][33][34][35], and assessment of the impact of COVID-19 on air quality and health (5 studies) [36][37][38][39][40]. Individual studies assessed the impact of AP episodes or extreme events, such as (Indian monsoon [13,31] or large forest fires and megafires in the center region of Portugal [41]), and the use of residential wood combustion in cities of Sweden, Finland, Norway, and Denmark [42].…”
Section: Motivation Of Conducted Studiesmentioning
confidence: 99%
“…All but six studies that applied AirQ did not report which type of AQMSs were used [47,[53][54][55][56][57]. For AirQ+, 74% of the studies (65 out of 88) gathered AAP data from the AQMSs, and only 16 studies reported the types of AQMSs used (Supplementary Tables S2, S3) [25,31,36,39,41,[58][59][60][61][62][63][64][65][66][67][68].…”
Section: Exposure Assessmentmentioning
confidence: 99%